2001
DOI: 10.1097/00005537-200101000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Nasal Function After Temperature‐Controlled Radiofrequency Tissue Volume Reduction for the Turbinate

Abstract: At 8 weeks postoperatively, the severity and the frequency of nasal obstruction improved subjectively in 81.3% and 93.8% of RFTVR group and in 87.5% and 87.5% of LVT group, respectively. Significant improvement of nasal symptoms began from 2 to 3 days after the operation in the RFTVR group, whereas there was significant improvement of nasal symptoms at 8 weeks after operation in the LVT group. However, objective nasal functions including nasal volume and total nasal resistance were significantly improved at 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
88
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 17 publications
(29 reference statements)
12
88
0
6
Order By: Relevance
“…The improvement may be attributed to the improvement in nasal patency following surgery. This finding is similar to other reported series [8,11]. Rhee et al [8] compared the effect of radiofrequency and laser reduction of inferior turbinate on olfactory improvement.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The improvement may be attributed to the improvement in nasal patency following surgery. This finding is similar to other reported series [8,11]. Rhee et al [8] compared the effect of radiofrequency and laser reduction of inferior turbinate on olfactory improvement.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to other reported series [8,11]. Rhee et al [8] compared the effect of radiofrequency and laser reduction of inferior turbinate on olfactory improvement. They found that after 8 post-operative weeks, half of the sample showed significant improvement in olfaction in both the groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Wound contraction by fibrosis results in submucosal tissue volume reduction and relief of nasal obstruction without causing damage to the overlying mucosa. Previous reports reflected that there is a recovery in patient-reported symptoms of obstruction with more than 90% improvement being achieved 8 weeks after treatment [6][7][8]. Mucociliary function is an important defense mechanism that protects the respiratory system against bacteria and other foreign particles.…”
Section: Introductionmentioning
confidence: 99%